EFFECTS OF COVID-19 LOCKDOWN ON URBAN FAMILY LIFE IN MARARABA SUBURB OF NASARAWA STATE, NIGERIA - Ambrose W. Ogidi; Philip Orlaade Abughul Orlaade Abughul; Mohammed Ayuba Oche Oche (International Studies Journal)
The emergence of Coronavirus in Nigeria and other countries of the world had far-reaching consequences, especially on the family as a social system. In the context of the Coronavirus as a public health pandemic, this study examined the effects of the Coronavirus on urban family life in the Mararaba suburb, in Karu Local Government Area of Nasarawa State. The study was exploratory and adopted the ethnographic thematic approach in the analysis of findings. The study employed the Frustration-Aggression Theory as a theoretical perspective. The Key Informant Interview guide was the primary instrument used in the collection of data from twenty-five family households selected through a multistage sampling technique. Findings revealed that the Covid-19 lockdown in the study area had far[1]reaching negative effects on the well-being of many urban families. These were in the aspects of irregular daily/monthly incomes, reduction in daily food consumption, and frequency of incidents of family conflict/violence among others. The study suggests social safety nets strategies such as increased farming activities through provisions of subsidized farming inputs to improve food production. Also, the need for urban families to create social security for themselves in form of increasing savings in the bank as well as investment in small-scale businesses such as poultry, and fish farming as alternative sources of livelihood in times of pandemic like the Covid-19.